Pengaruh Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian Produk Skincare - Tiara Apriani; Halimah Zahrah (Indo Publishing, 2026)
The growth of the beauty industry has changed the way consumers buy products. Product quality and brand image greatly influence purchasing decisions for skincare products. This study analyzes how product quality and brand image affect management students of the 2023 class at Muhammadiyah University Bandung. The method used is quantitative research with 126 respondents selected through purposive sampling. Data was collected through a questionnaire that had been tested for validity and reliability. The results showed that product quality had a positive and significant effect on purchasing decisions, as did brand image. Overall, both contributed greatly to purchasing decisions. The study concluded that good product quality and a strong brand image are important for increasing purchasing decisions. It is recommended to continue maintaining product quality and building a positive brand image.